INVESTIGATION OF WIND ENERGY POTENTIAL IN KARTALKAYA-BOLU, TURKEY - Ucar, Aynur; Balo, Figen (Taylor & Francis Inc, 2009)
In this study, wind characteristics and the wind energy potential of the Kartalkaya skinning center in the west of the Black Sea region of Turkey were analyzed using wind speed data collected during the period from 2000 to 2006. The wind speed distribution curves of the investigated location were obtained by using the Weibull and Rayleigh probability density functions based on these data. Weibull shape parameter k and scale parameter c were found to be 1.79 and 6.64 m/s for the period from 2000 to 2006. A yearly mean wind speed of 5.90 m/s was obtained in Kartalkaya-Bolu for the 7-year period. However, the mean power density based on the Weibull function is 303 W/m(2). The results show that the investigated location has available wind energy potential.
Keywords: Wind energy; Wind data; Weibull distribution; Turkey